Introduction - Marieke Venselaar (A+BE: Architecture and the Built Environment, 2018)
The construction industry is known for its waste of money and materials, low innovative capacities, and low productivity (Cox and Thompson, 1997; Vrijhoef, 2011). One reason for that inefficiency is the antagonistic relationship between clients and contractors (Tazelaar and Snijder, 2010; Vrijhoef, 2011). Clients often use competitive procurement and selection procedures to select contractors (Boukendour and Hughes, 2014). These procedures are expensive and time-consuming both for the contractor and the client. The contractor does not necessarily earn back this investment, since there is a chance that he will not be given the assignment. Therefore, sometimes contractors feel a need to bid unrealistically low, sometimes even below the cost price. Often throughout the realization of the project, failures accumulate and may accordingly result in a heavier workload, higher costs, longer project duration and lower quality.